Cultural differences affect interactive television advertising. Issue 1 (2nd January 2016) - Zorn, Steffen Frank; Bellman, Steven; Robinson, Jennifer A.; Varan, Duane
Abstract : Comparing results from the UK and the USA, this study shows that even subtle cultural differences between two very similar countries can affect new forms of advertising such as interactive television (iTV) commercials. The UK pioneered the mainstream use of iTV advertising, and now it is a mainstream advertising option in the USA on cable networks and online TV networks like Hulu. This study tests whether effective iTV-ad execution factors identified by a previous study of 500 UK iTV campaigns are similarly effective in the USA based on data from 257 iTV campaigns run on the experimental Wink platform between 1998 and 2004. It finds that specific cultural differences make iTV advertising in the USA unique, but also identifies potential globally effective universals for iTV ads. The results of this study allow advertisers to predict the most effective alternative ideas for iTV advertising campaigns run in the USA and potentially in other countries around the world.